Destino do carbono de raízes e parte aéreas de culturas de inverno enriquecidas com 13C em solo sob plantio direto - Tahir, Majid Mahmood (2015)
Little is known about the decomposition and stabilization of shoots and intact roots derived carbon (C) under no-tillage (no-till) field conditions. The present study was designed with following objectives: 1) evaluation of 13C pulse labeling method to label crop plants under field conditions for subsequent C dynamics studies, 2) estimation of the actual rates of mineralization of intact roots and shoot residues, decomposing simultaneously, and 3) finally to determine the fate of shoot vs root residues derived C in soil, under no-till field conditions. The experiment was conducted at Federal University of Santa Maria , Rio Grande de Sul, Brazil in 2013-2014 in an loam textured Typic Paleudalf. Wheat (Triticum aestivum L.), pea (Pisum sativum L.) and vetch (Vicia sativa L.) plants were grown inside polyvinyl chloride (PVC) cylinders and were pulse labeled weekly with 13C in the field until the flowering stage. At plant harvest, the biomass of shoots and roots and chemical composition and isotopic enrichment was determined. In order to achieve second objective, paired treatments were designed by combining 13C labeled shoots with unlabeled roots+soil and unlabeled shoots with 13C labeled roots+soil for each crop, plus a control treatment. For the third objective, soil cylinders were excavated after 60, 180 and 365 days for the determination of distribution of shoot and root derived Cnew in soil aggregates. The chemical composition of plant tissues (shoot and roots) were not modified by 13C labeling. The maximum level of 13C enrichment in plants at harvest, was +495 in wheat, +426 in pea and +378 in vetch plants. Our results though demonstrated heterogeneity of 13C among plant parts particularly between stems and leaves however, it was far less than reported in other field and controlled conditions experiments. The mineralization of roots+soil C was higher than shoot-C residues for the three species (73 vs. 45 % initial C for wheat, 76 vs. 48 % for pea and 73 vs. 51 % for vetch). Remaining 13C in root and soil organic matter (SOM) at day 180 indicated both a higher rate of root-C decomposition and a higher rate of root- derived C in SOM compared to shoots. Greater proportion of the shoot and root derived Cnew of three crops was associated with large macroaggregates (>2000 μm) in 0-5 cm soil layer which declined with time. The content of root and shoot derived C microaggregates (53 250 μm) increased gradually with time in all the three soil for all crops. After 365 days, 30% of the root derived C was present in soil compared to 5 % (average of three crops) of the shoot derived C. The mean relative contribution of root vs shoot derived Cnew was 2.1 ranging from 1.5 (pea) to 2.5 (wheat). Our findings suggest that, crop residues location and contact with soil and, the soil moisture and temperature, are important factors that significantly promoted roots decomposition and root derived C in soil in situ, compared to shoots, erasing the consequences of their different initial chemical composition. The 13CO2 labeling technique used under the field appeared to be a practical approach with respect to resource demand and is suitable for in situ labeling. This work provides a framework for further studies focusing on the interactions between aboveground and belowground crop residues and environmental factors under no-till field conditions.